Identyfikacja obserwacji oddalonych z wykorzystaniem metody wektorów nośnych - Trzęsiok, Michał (Novelty Detection with Support Vector Machines, 2007)
Support Vector Machines (SVM) are considered as a robust tool for classification. This method is designed for being able to deal with outliers. In the paper Support Vector Machines for single-class problems are presented and the impact of removing previously identified outliers on the classification test set error is analyzed on benchmarking data sets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 350-357